The effectiveness and safety of ixekizumab in psoriasis patients under clinical practice conditions: A Spanish multicentre retrospective study. Issue 6 (3rd September 2020) - Rivera, Raquel; Velasco, Manuel; Vidal, David; Carrascosa, J. Manuel; Daudén, Esteban; Vilarrasa, E; Notario, Jaime; Ruíz‐Villaverde, Ricardo; Yanguas, Ignacio; García‐Latasa, Francisco Javier; Ferrán, Marta; Lázaro‐Simó, Anna; et al.
Abstract: The objective of the study was to evaluate efficacy and safety of ixekizumab in psoriasis patients under clinical practice conditions. Observational, retrospective, multicentre study that included patients with ixekizumab from March 2017 to March 2019. ≥ 90% reduction in the Psoriasis Area and Severity Index (PASI 90) and absolute PASI <2 were the parameters used to assess treatment response. Adverse events (AEs) were collected. Of the 301 patients included, 111 were women (36.9%), mean age was 48.5 (±13.5) years. Mean baseline PASI score was 13.5 (±7.7). More than half of the patients (68.5%) had received at least one biological drug before. At 3 months, 208 (76.5%) patients achieved PASI <2 and 156 (57.3%) PASI 90. At 12 months, 130 (73.4%) patients achieved absolute PASI <2 and 104 (58.7%) PASI 90. Multivariate analysis revealed that prior use of biologics was influential in achieving PASI <2 at both 3 and 12 months (OR 2.82, P = .006; OR 9.51, P < .001, respectively). Sixty‐five patients (21.59%) exhibited at least one AE, injection site reaction was the most common (39; 36.8%). Likewise in trials, ixekizumab displayed an excellent profile of safety and efficacy also in real‐life. Effectiveness appears superior in biologic‐naive patients.